Endoctriner et radicaliser sur la Toile - Mathieu Colin; Solange Lefebvre; Dianne Casoni (Communication)
This paper discusses the findings of research on the political far right aimed at analyzing the multiple links between the media and radicalization leading to violence. The research team used a number of quantitative and qualitative methodologies based on interviews with some 70 radicalized individuals and direct observations of events that bring their groups together. The paper examines the explicit statements of two radicalized individuals and presents an analysis of the hundreds of sites visited over many months between 2018 and 2020.